Pengaruh Penggunaan Pupuk Kotoran Kambing dan Pupuk Organik Cair Limbah Sayuran untuk Meningkatkan Pertumbuhan dan Produktivitas Tanaman Seledri (Apium Graveolens L.) - Irvan Gilang Syahputra Sitepu; Desi Sri Pasca Sari Sembiring; Najla Lubis (Jurnal Riset Rumpun Ilmu Tanaman, 2025)
The purpose of this study was to determine the effect of the application of goat manure and liquid organic fertilizer derived from vegetable waste on the growth and productivity of celery plants (Apium graveolens L.). This study used a factorial Randomized Block Design (RBD) consisting of two factors with 48 plots.The first factor was the application of goat manure fertilizer, symbolized as “G”, which consisted of four treatment levels: G0 = 0 g/polybag, G1 = 200 g/polybag, G2 = 400 g/polybag, and G3 = 600 g/polybag.The second factor was the application of liquid organic fertilizer from vegetable waste, symbolized as “S”, which consisted of four treatment levels: S0 = 0 ml, S1 = 100 ml/L of water, S2= 200 ml/L of water, and S3 = 300 ml/L of water.The parameters observed were plant height, number of leaves, leaf width, number of tillers, plant weight per polybag, and plant weight per plot. The results of the study showed that the application of goat manure and liquid organic fertilizer from vegetable waste had a significant effect on the parameters of plant height, number of leaves, leaf width, number of tillers, plant weight per polybag, and plant weight/plot.